Cooperation of Coordinative and π···π Interaction in Directing Two‐fold Interpenetrated Architecture of Two Eu/Dy(III) 2‐Sulfoterephthalate Complexes with 4, 4′‐Bipyridine1. Issue 3 (4th February 2015) - Ren, Yi‐Xia; An, Miao; Chai, Hong‐Mei; Zhang, Mei‐Li; Wang, Ji‐Jiang
Abstract: Two novel lanthanide coordination polymers, [Ln(stp)(bipy)(H2 O)]· (H2 O) n [Ln = Eu (1 ) and Dy (2 )], were synthesized by hydrothermal reactions of 2‐sulfoterephthalate (stp) and 4, 4′‐bipyridine (bipy) ligands with europium/dysprosium(III) salts. Structural analyses show that both complexes1 and2 are isomorphic and crystallize in the monoclinic crystal system with space group P 21 / n . Complex1 exhibits a two‐dimensional grid‐like structure from europium(III) ions bridged by the carboxyl and sulfonate groups of stp ligands. Notably, the stretching 4, 4′‐bipyridine ligands besides the 2D grid‐like layers form π··· π interactions and interpenetrate into the empty voids of another adjacent layer into a twofold interpenetrated structure. Fluorescence analysis show that the emission of two complexes exhibit the characteristic peaks of lanthanide ions. Abstract :